2018
DOI: 10.3390/ijms19092585
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β and BMPR2 Signaling in PAH: Two Black Sheep in One Family

Abstract: Knowledge pertaining to the involvement of transforming growth factor β (TGF-β) and bone morphogenetic protein (BMP) signaling in pulmonary arterial hypertension (PAH) is continuously increasing. There is a growing understanding of the function of individual components involved in the pathway, but a clear synthesis of how these interact in PAH is currently lacking. Most of the focus has been on signaling downstream of BMPR2, but it is imperative to include the role of TGF-β signaling in PAH. This review gives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 134 publications
2
70
0
Order By: Relevance
“…Upon binding to bone morphogenetic proteins (BMPs), BMPR2 initiates intracellular signaling that ultimately leads to the inhibition of proliferation of vascular smooth muscle tissue. In smooth muscle cells, BMP signaling can be directly inhibited by TGF-β signaling and involved ligands are able to function as antagonists in competition for type II receptor binding [123]. BMPR2 loss-of-function mutations are a known cause for PAH development in patients and lead to more severe disease and increased risk of death when compared to PAH patients without a BMPR2 mutation [124].…”
Section: Immunomodulatory Therapy In Pah and Ctephmentioning
confidence: 99%
“…Upon binding to bone morphogenetic proteins (BMPs), BMPR2 initiates intracellular signaling that ultimately leads to the inhibition of proliferation of vascular smooth muscle tissue. In smooth muscle cells, BMP signaling can be directly inhibited by TGF-β signaling and involved ligands are able to function as antagonists in competition for type II receptor binding [123]. BMPR2 loss-of-function mutations are a known cause for PAH development in patients and lead to more severe disease and increased risk of death when compared to PAH patients without a BMPR2 mutation [124].…”
Section: Immunomodulatory Therapy In Pah and Ctephmentioning
confidence: 99%
“…Although the pathogenesis of PAH is not completely understood, it has been reported that the genetic change resulting in endothelial dysfunction is an important contributing factor (2,3). Previous studies have revealed that bone morphogenetic protein type II receptor (BMPR2) mutations serve an important role in PAH pathogenesis via the Smad and transforming growth factor-β signaling pathways (4)(5)(6). However, as PAH is not penetrant, BMPR2 mutations alone may not be sufficient to cause disease, therefore, other genetic and/or non-genetic factors may serve as a 'second hit' to trigger PAH pathology (7), including inflammation and chronic hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…increased glucose uptake and utilization by glycolysis and the pentose shunt in diseased pASMcs. We began by assessing the uptake and utilization of [1,2,[3][4][5][6][7][8][9][10][11][12][13] C 3 ]glucose in diseased versus control PASMCs. Glucose labeled at carbons 1-3 allows the comparative assessment of glucose metabolism through glycolysis versus the pentose shunt.…”
Section: Resultsmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ disease and schistosomiasis [11][12][13] . TGF-β induces cellular phenotypes which require energy and metabolic substrates, including proliferation, migration, contraction, and synthesis of cytokines and the extracellular matrix.…”
mentioning
confidence: 99%